Pengaruh ukuran perusahaan, solvabilitas dan reputasi kap terhadap audit delay pada perusahaan property & real estate di Bursa Efek Indonesia periode 2009-2012 - Indah Permata Sari; Raja Adri Satriawan; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to analyze the effect of firm size, solvency and reputation of the firm to audit delay in property & real estate companies in Indonesia Stock Exchange Period 2009-2012.The population in this study are all property and real estate company listed on the Indonesia Stock Exchange (IDX) 2009-2012. The population was 52 companies, but based on the above criteria there are 49 (forty nine) companies. Analysis of data using multiple linear regression.The study states that the size of the company does not have a significant impact on audit delay. It can be seen from the t value (0.649) obtained is smaller than t-table (1.973), the independent variable has no effect on the dependent variable so that the first hypothesis (H1) is not acceptable. Debt to Equity Ratio has a significant effect on audit delay. It can be seen from DER variable t value (2.449) is greater than t-table (1.973) then has the effect of independent variables on the dependent variable, thus the first hypothesis (H2) is acceptable. Public accounting firm's reputation has a significant impact on audit delay. It can be seen from the t value (2.117) is greater than t-table (1.973) then has the effect of independent variables on the dependent variable so that the third hypothesis (H3) is received.Keywords: Company Size, Debt to Equity Ratio, Reputation Public Accounting Firm, Audit Delay